3D subsurface temperature model of Europe for geothermal exploration: - Limberger, J.; Wees, J.D. van (EAGE Publishing BV, 2014)
For the assessment of geothermal resources in Europe we constructed a digital 3D temperature model of the European crust and sedimentary basins, incorporating publicly available temperature data. Using European crustal thickness models and indirect parameters such as surface heat flow measurements, temperatures were calculated for regions where data are scarce. Our temperature model of Europe has a horizontal grid resolution of 10x10 km and extends to a depth of 10 km below ground level. The model covers Europe up to the Russian border and includes Turkey and Iceland.